Scurvy diagnosis due to gingival alterations: Case report - Lima, Bruna Ferreira de; Luz, Thais Oliveira da; Martins, João Roig; Daroit, Natália Batista (Journal of Oral Diagnosis, 2023)
Introduction: Scurvy is a disease resulting from a severe vitamin C deficiency, and its diagnosis is often challenging owing to nonspecific symptoms. Objective: encouraging dentists to reflect on systemic causes that may influence the oral manifestations of diseases. Emphasize that despite a disease from the last century, today you can still find vitamin deficiencies, and report of a case of Scurvy with gingival alterations. Case Report: A 30-year-old female patient sought dental care because she experienced sensitivity in her gums and bleeding. Intraoral examination revealed a slightly swollen gingiva which was erythematous, with friable consistency, and bled upon probing. Diseases such as anemia, hypovitaminosis, and AIDS, were considered within the diagnostic hypothesis of gingivitis. After hematological investigation, a very low level of vitamin C was detected, and scurvy was diagnosed. Vitamin C supplementation was then initiated in addition to the control of oral hygiene. After four months, clinical improvement was observed. Conclusion: Althou-gh there are few cases in the literature, oral surgeons must be aware of oral alterations associated with scurvy. The search for local and systemic etiological factors is important because changes in general health have a direct impact on oral tissues.